PENGARUH OTORITAS PEMIMPIN DAN UNCERTAINTY ENVIRONTMENT TERHADAP BUDGETARY SLACK - Erwin Tanjaya; Marini Purwanto (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2023)
Budgetary slack is the tendency of management to intentionally lower revenues or higher costs. Budget slack can cause losses for the company because the company's performance is less than optimal in determining the targets to be achieved. This action is influenced by various factors such as the authority of the leader and the uncertainty of the environment. This research is an experimental study to examine the influence of the leader's authority and uncertainty environment on the occurrence of budgetary slack. The object of this research is the undergraduate students majoring in Accounting at Widya Mandala Catholic University Surabaya as many as 64 participants, using a 2x2 experimental design. Participants were divided into 4 different cells which were given different treatments. The ANOVA test tool is used to test the results of the data that has been collected in order to test the predetermined hypothesis. Before carrying out the ANOVA test, a Levene test will be carried out to determine the level of homogeneity of the data that has been collected, if the data is not homogeneous then the data cannot be used to continue the test. The results of this test prove that leaders who use coercive power encourage subordinate behavior to do budgetary slack compared to leaders who use legitimate power. For environmental uncertainty variables, subordinates who are in low environmental uncertainty tend to do budgetary slack compared to subordinates who are in high environmental uncertainty.